Respuesta :

Answer:

1.a=2

2.  C  x=2  and x=-3

Step-by-step explanation:

The standard form for the quadratic function is  

ax^2 +bx+c

so  we need to rewrite the function to be in this form

2x^2 -10 = 7x

Subtract 7x from each side

2x^2 -7x-10 = 7x-7x

2x^2 -7x-10 = 0

a =2, b= -7  c=-10


2.  The quadratic formula is

-b ± sqrt(b^2 -4ac)

----------------------------

2a


2x^2 + 2x=12

Lest get the equation in proper form

2x^2 + 2x-12 = 12-12

2x^2 +2x-12 =0

a=2  b=2 c=-12

Lets substitute what we know

-2 ± sqrt(2^2 -4(2)(-12))

----------------------------

2(2)

-2 ± sqrt(4+96)

----------------------------

2(2)

-2 ± sqrt(100)

----------------------------

4

-2 ± 10

----------------------------

4

-2 + 10               -2-10

-----------   and  --------------

4                             4

8/4   and -12/4

2  and -3

ACCESS MORE